“Project TUBIG PARA SA LAHAT (Water for All)”: A Community Based Action Research - Asio, John Mark R.; Gadia, Ediric D.; Cura, Carlmaulen J.; Soriano, Imelda DP. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This paper aims to present the community extension project of local higher education in Olongapo City, Philippines. The project entitled “Project Tubig Para sa Lahat (Water for All).” is a collaborative effort of the Gordon College – Community Extension Service Unit (GC –CESU) and different Non-Government Organizations (NGOs). The project's main objective is to provide a clean water storage for every household in a far-flung community in Olongapo City. This project is an initial step towards the United Nations Sustainable Development Goals (UN SDGs) mandate, in particular SDG 6. After a series of meetings, a strategic planning, and months of preparation, the project commenced. However, there were some challenges in the logistics due to the distance and terrain of the place. Nevertheless, the project was successful and turned over to the community as a sign of community engagement to all parties involved. The whole community has full access to the water tank project, and many households benefitted from the said project.